Asuhan Kebidanan Komprehensif Pada Ny. P Mulai dari Hamil, Bersalin, Nifas, Bayi Baru Lahir dan Keluarga Berencana di Klinik Pratama Riyyan Kaban Jahe Tahun 2021/2022 - Linda Purwanti (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Pregnancy is a physiological and natural condition that occurs in women. There are various complaints experienced by pregnant women during their pregnancy, one of the most common complaints is dizziness. Objective: LTA provides comprehensive midwifery care to pregnant, maternity, postpartum, BBL, neonate and family planning women using a midwifery management approach for Mrs "P" who complained of dizziness. Method: Care in this LTA is through interviews, observation and care management. The subject in this care is Mrs "P" at the Pratama Riyyan Kabanjahe Clinic. Results: results of comprehensive midwifery care for Mrs "N" during pregnancy in the second trimester and third trimester with dizziness, in normal labor, spontaneously without complications, in the postpartum period with normal puerperium, in BBL with BBLN, in patients.